The Correlations Between One's Readiness and The Level of Anxiety When Facing OSCE Exam Among the Students of Nursing Undergraduate Study Program, Respati University Yogyakarta - mohamad judha (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Background: Anxiety is a mood disorder characterized by fears and worries over something. It includes fears and worries about exams which then make someone get prepared for the exams. Previous research conducted on November 14, 2014 found that OSCE was an exam that triggered tenseness, fears, restlessness, and worries. Objectives: This research is to find out the correlations between one's readiness and the level of anxiety when facing OSCE exam among the students of Nursing Undergraduate Program, Respati University Yogyakarta. Research Methodology: This research was a descriptive correlational one with a cross sectional design. A simple random sampling method was used to collect the data from as many as 68 people. The data were collected using questionnaires on April 24 and 26, 2021. The data were then analyzed by the kendal tau analysis. Results : The results indicate that as many as 34 respondents (50%) of 18 years old and as many as 56 female respondents (82.4%) showed the level of anxiety and readiness when facing the OSCE exam. Those having a medium level of readiness were 45 people (66.2%) and those who have a serious level of anxiety were 44 people (64.7%). The statistical analysis indicates that the p-value is 0.037 0.05) with the level of low homogeneity of -0.246. Conclusion: There was a positive correlation between one's readiness and the level of anxiety when facing the OSCE exam among the students of Nursing Undergraduate Program, Respati University Yogyakarta.